Effect of Wheat Gluten on The Quality Attributes of Plant-Based Meat Analogue Formulated with Pea, Soy and Pumpkin Seed Flours - Adhikari, Babita; Bhattarai, Sayuj; Dahal, Lekhraj (Himalayan Journal of Science and Technology, 2024)
This study explores the effect of wheat gluten on the quality attributes of plant-based meat analogues (PBMAs) formulated with pea, soy, and pumpkin seed flours. PBMAs were developed with varying gluten levels (0–40 parts), and analyzed for moisture, protein, fat, fiber, ash content, pH, cooking loss, water holding capacity (WHC), swelling capacity (SC), and sensory attributes. WHC is defined as the maximum amount of water a given quantity of material can retain, making it a critical quality attribute associated with freshness and the proteins' ability to form a cohesive gel network. SC is the volume occupied by a known weight of a food after it has absorbed water and reached equilibrium without dissolution. Protein content significantly (p